The Role of Human Resource Planning, Demographic Change and Advances in Information Technology in Management Education (Literature Review Thinking System) - Kurniawaty, Ria; Kemas Imron Rosyadi (Dinasti International Journal of Digital Business Management, 2022)
Literature Review article (Education Management): (Human Resources), (demographic change) and (Information Technology Progress): is a scientific article that aims to build a hypothesis of Inter-variable role research that will be used in subsequent research, within the scope of Education Management Science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) HR planning plays a role in the implementation of Education Management; 2) demographic change plays a role in the implementation of Education Management; and 3) The Advancement of Information Technology plays a role in the implementation of Management Education. Apart from these 3 exogenous variables that play the role of endogenous variables in Education Management, there are many other factors.